Effects of Evolocumab on Mortality Outcomes in Patients Without Previous Myocardial Infarction or Stroke: A Prespecified Analysis of the VESALIUS-CV Randomized Clinical Trial - Robert P. Giugliano; Erin A. Bohula; Andrea Bellavia; Gaetano M. De Ferrari; Lawrence A. Leiter; Jose C. Nicolau; Ajay K. Bhatia; Sabina A. Murphy; Lyrica Liu; Huei Wang; Vladimir Blaha; Andrejs Erglis; et al. (Circulation, 2026)
BACKGROUND: Evolocumab, a PCSK9 (proprotein convertase subtilisin–kexin type 9) inhibitor, significantly reduced the risk of cardiovascular events in patients without previous myocardial infarction or stroke in the VESALIUS-CV trial (Effect of Evolocumab in Patients at High Cardiovascular Risk without Prior Myocardial Infarction or Stroke). However, mortality results have yet to be fully characterized. METHODS: VESALIUS-CV was a double-blind study of 12 257 patients (median age, 66 years [interquartile range, 60–71]; 43% women) with qualifying atherosclerosis or high-risk diabetes without previous myocardial infarction or stroke, and low-density lipoprotein-cholesterol ≥90 mg/dL (or non–high-density lipoprotein-C ≥120 mg/dL or apolipoprotein B ≥80 mg/dL) who were randomized to evolocumab or placebo. Prespecified mortality outcomes of interest included all-cause mortality, subtypes of death (including cardiovascular [CV] and non-CV), and timing of events. Non-CV mortality was further investigated using multistate modeling to assess the contribution of prevention of nonfatal CV events (myocardial infarction, ischemic stroke, and ischemia-driven arterial revascularization) to non-CV mortality. RESULTS: Over a median of 4.6 years (interquartile range, 4.0-5.2), 973 (7.9%) patients died: 351 (36%) of CV causes, 497 (51%) of non-CV causes, and 125 (13%) of undetermined cause. All-cause mortality rates were 20% lower with evolocumab compared with placebo: 434 deaths (5-year Kaplan-Meier rate of 7.9%) with evolocumab versus 539 deaths (9.7%) with placebo (hazard ratio, 0.80, 95% CI, 0.70–0.91; P =0.0005). There was consistency of benefit for CV death (156 deaths [2.8%] versus 195 [3.6%]; hazard ratio, 0.79; 95% CI, 0.64–0.98), non-CV death (229 [4.2%] versus 268 [5.0%]; hazard ratio, 0.85; 95% CI, 0.71–1.01), and deaths of undetermined cause (49 [1.1%] versus 76 [1.4%]; hazard ratio, 0.64; 95% CI, 0.45–0.92). Results were consistent regardless of age, sex, region, race, qualifying atherosclerosis or high-risk diabetes, baseline low-density lipoprotein-cholesterol, or background lipid therapy. Postrandomization nonfatal myocardial infarction, ischemic stroke, and ischemia-driven arterial revascularization were associated with increased risk of subsequent non-CV death within the next 4 years, with the majority occurring during the first year after the event. Multistate modeling suggested the observations regarding non-CV death with evolocumab was largely (78%; bootstrap interquartile range, 71–92%) driven by the prevention of antecedent nonfatal CV events. CONCLUSIONS: These results support using evolocumab to improve survival in high-risk patients who have not experienced a previous myocardial infarction or stroke, including those with high-risk diabetes without qualifying atherosclerosis with low-density lipoprotein-cholesterol ≥ 90 mg/dl (or non-high-density lipoprotein-cholesterol ≥ 120 mg/dl or apolipoprotein B ≥ 80 mg/dl). REGISTRATION: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03872401.